Att läsa nazism ur vardagen : en biografisk ideologianalys av Sven Arvid Florys dagboksskrivande 1932–1941. - Nordanskog,Arvid (2025)
A biographical ideology-analysis of Sven Arvid Flory’s diaries, 1932‒1941. This study follows the diaries of the Swedish officer Sven Arvid Flory from 1932 through 1941, analysing the political and personal notes made and relating them to broader frameworks of ideology. First impressions of the material hinted at nazi sympathies. The study then focused on these ideological aspects of the diaries, in an attempt at categorising and understanding Flory’s ideology as a part of a wider ideological landscape. The intent of this study was partly to complement collective definitions of ideology, but more importantly also to reach a deeper understanding of Sven Arvid Flory both as a person, and as a reflection of the Swedish ideological landscape in which his convictions were formed. The results show an increased presence of politics in the material as the years go on, especially in the last few years when the Flory draws direct and antisemitic parallels between “jews” and Anglo-American capitalism against which only Germany (under Hitler) stands. Flory’s opposition against communism is a consistent thread throughout the years, though his views become somewhat more nuanced over time as he shows more tolerance of French and Spanish communists compared to “Russians”. Antisemitic remarks are also recurring but change over time to become more aggressive and take up more of the contents of the diaries. Flory expresses a conspiratorial and often abstract antisemitism targeted at “Jewish” capitalism and democracy, while the violence of contemporary antisemitism may have unsettled him. Flory’s distaste for democracy is also rather abstract, as he seems mostly content with the Swedish society he lives in and especially with the leadership of prime minister Per Albin Hansson. Flory also never joined any nazi party, as far as the study shows. The ideology expressed in the diaries is certainly antisemitic, pro-German and sympathetic to Nazism, but not outright national socialist until at the earliest 1940, and even then there’s a debate to be had. An important conclusion of the study is thus the complexity of ideology as expressed by individuals, which can often be more nuanced and contradictory than definitions outlined in theory. As a prism, Flory’s diaries highlight these idiosyncrasies as well as the multifaceted ideological landscape of interwar Sweden, heavily influenced by rapid and dramatic shifts in contemporary European politics, such as the Spanish Civil War, the Soviet invasion of Finland, the rise of Hitler and the outbreak of the Second World War.
Keywords: historical biography; biographical prism; microhistory; personal ideology; interwar era Sweden; Swedish military history; antisemitism; Nazism